2016
DOI: 10.1038/nn.4319
|View full text |Cite
|
Sign up to set email alerts
|

SHANK3 controls maturation of social reward circuits in the VTA

Abstract: SummaryHaploinsufficiency of SHANK3, encoding the synapse scaffolding protein SHANK3, leads to a highly penetrant form of Autism Spectrum Disorder (ASD). How SHANK3 insufficiency affects specific neural circuits and this is related to specific ASD symptoms remains elusive. Here we used shRNA to model Shank3 insufficiency in the Ventral Tegmental Area (VTA) of mice. We identified dopamine (DA) and GABA cell-type specific changes in excitatory synapse transmission that converge to reduce DA neuron activity and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
133
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 53 publications
11
133
1
Order By: Relevance
“…Importantly, similar effects have been demonstrated when animals experience stress during neurodevelopmental periods, such as for example, peripubertal stress inhibits social interactions during adulthood. Stressors during both developmental periods and adulthood lead to changes in neuronal networks . It has thus been shown that peripubertal stress results in modulations of gene and cell adhesion molecule expression in prefrontal cortex (PFC) during adulthood, and adulthood stressors also modulate hippocampal functioning .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, similar effects have been demonstrated when animals experience stress during neurodevelopmental periods, such as for example, peripubertal stress inhibits social interactions during adulthood. Stressors during both developmental periods and adulthood lead to changes in neuronal networks . It has thus been shown that peripubertal stress results in modulations of gene and cell adhesion molecule expression in prefrontal cortex (PFC) during adulthood, and adulthood stressors also modulate hippocampal functioning .…”
Section: Introductionmentioning
confidence: 99%
“…Stressors during both developmental periods and adulthood lead to changes in neuronal networks . It has thus been shown that peripubertal stress results in modulations of gene and cell adhesion molecule expression in prefrontal cortex (PFC) during adulthood, and adulthood stressors also modulate hippocampal functioning . Both hippocampus and PFC are also involved in cognitive and emotional processing of stress stimuli, and both hippocampus and PFC mediate the symptoms of depression and anxiety .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mGlu 1 knock out mice show disrupted prepulse inhibition similar to that seem with mGlu 5 knock out mice (Brody et al, 2003; Brody et al, 2004). Future studies with newly developed mGlu 1 tools (Cho et al, 2014; Lovell et al, 2013) will provide critical insights into the biological roles and therapeutic potential of mGlu 1 in treating schizophrenia, and other disorders in which mGlu 1 has been implicated, including ataxia, substance abuse, and autism spectrum disorders (Bariselli et al, 2016; Lum et al, 2014; Power et al, 2016). …”
Section: Potential Utility Of Mglu1 Pams For Treatment Of Schizophreniamentioning
confidence: 99%
“…These synaptic changes occur together with reduced in vivo burst activity of DA neurons and behavioral deficits, including impaired social preference dynamics. Moreover, since post‐natal systemic treatment with a positive allosteric modulator (PAM) of mGluR1 rescued synaptic alterations and ameliorated neuronal activity and social deficits (Bariselli et al, ), we provided a link between altered DA neuron activity and social behavior. In fact, while synaptic deficits were also present at GABA neuron synapses, they were not rescued by PAM‐mGluR1 treatment and the optogenetic activation of VTA DA neurons was per sé sufficient to overcome shShank3‐induced behavioral impairment.…”
mentioning
confidence: 99%
“…We have previously shown that the post‐natal downregulation of proline‐rich containing isoforms of SHANK3 changes synaptic properties onto DA neurons in the VTA (Bariselli et al, ). Animal models with constitutive mutations or deletion of the proline‐rich domain (Kouser et al, ; Speed et al, ) show decreased basal excitatory synaptic transmission in the hippocampus, but the AMPA and NMDA subunit composition has not been electrophysiologically analyzed.…”
mentioning
confidence: 99%